Small Signal Modeling and Performance Analysis of Conventional- and Dual-UPQC - Shuqi Shi; Dashuang Liu; Jian Han (IEEE Access, 2024)
Both the conventional and dual compensation strategies are widely adopted in a unified power quality conditioner (UPQC). However, the differences between them are lack of in-depth analysis. This article establishes the small signal models in dq-axis of conventional- and dual-UPQC (C- and D-UPQC) with consideration of the effects of the phase-locked-loop (PLL) and grid impedance, which lays the foundation for static and dynamic performance analysis. In addition, the performance of them is analyzed and compared under different conditions. It is found that: the D-UPQC has a better dynamic performance when the grid voltage or load suffers sudden variation; the harmonic rejection capabilities of the C- and D-UPQC are different; the grid impedance has an obvious influence on the load voltage quality in the C-UPQC. The findings will provide the guideline for the selection of compensation strategies in specific applications. Finally, experimental results verify the correctness of the comparative performance analysis.